2021
DOI: 10.1016/j.isci.2021.102968
|View full text |Cite
|
Sign up to set email alerts
|

Combustion ion chromatography for extractable organofluorine analysis

Abstract: Summary Combustion ion chromatography (CIC) has found a role in environmental analytical chemistry for fluorine content analysis. It is used for extractable organofluorine (EOF) analysis to evaluate perfluoroalkyl and polyfluoroalkyl substances (PFASs) and other organofluorine burden. The prevailing assumption has been that all PFASs are incinerated in CIC and matrix components have no impact on this process, but this has not been experimentally evaluated. In this work, the combustion efficiencies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 37 publications
0
15
1
Order By: Relevance
“…These methods either require extra pre-treatment steps or often have relatively low effectiveness because of high matrix effects like groundwater contaminants and common environmental co-contaminants. Recently, combustion ion chromatography (IC), where compounds are combusted and their fluorides are run through an IC system has been successfully adapted to quantify PFAS [20][21][22]. However, these methods do not analyze individual PFAS and quantify them.…”
Section: Introductionmentioning
confidence: 99%
“…These methods either require extra pre-treatment steps or often have relatively low effectiveness because of high matrix effects like groundwater contaminants and common environmental co-contaminants. Recently, combustion ion chromatography (IC), where compounds are combusted and their fluorides are run through an IC system has been successfully adapted to quantify PFAS [20][21][22]. However, these methods do not analyze individual PFAS and quantify them.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that some low PFAS recoveries may be due to incomplete combustion. 26 To evaluate the possibility of incomplete combustion, 10 analytes with mean recoveries ≤70% (FDEA, FDUEA, 10 : 2 FTS, PFTrA, FDET, 11Cl-PF3OUdS, N-Me-FOSE, N-EtFOSE, trifluralin, and oxyfluorfen) on the APU sim were spiked directly from the individual stocks onto the top GAC and dried in a 55 °C oven for 10 minutes to evaporate the methanol. The top GAC column was then placed in a column holder along with a bottom GAC column and washed with 8.2 g L −1 KNO 3 .…”
Section: Resultsmentioning
confidence: 99%
“…These data are in reasonable agreement with a prior study investigating combustion efficiencies of 13 PFAS, which showed consistent combustion efficiency for most substances. 43 Overall, combustion efficiencies for inorganic and organic F, Cl, and Br, were sufficiently accurate and precise for carrying out OHC mass balance experiments, although there is a need for EOX interlaboratory studies and reference materials to further standardize these methods for widespread use.…”
Section: Quality Control Of Halogen Mass Balancementioning
confidence: 97%